Molecular Analysis of East African Lumpy Skin Disease Viruses Reveals a Mixed Isolate with Features of Both Vaccine and Field Isolates - Tesfaye Rufael Chibssa; Melaku Sombo; Jacqueline Kasiiti Lichoti; Tajelser Idris Badri Adam; Yang Liu; Yazeed Abd Elraouf; Reingard Grabherr; Tirumala Bharani K. Settypalli; Francisco J. Berguido; Angelika Loitsch; Mesfin Sahle; Giovanni Cattoli; et al. (Microorganisms, 2021)
Lumpy skin disease (LSD), an economically significant disease in cattle caused by lumpy skin disease virus (LSDV), is endemic to nearly all of Africa. Since 2012, LSDV has emerged as a significant epizootic pathogen given its rapid spread into new geographical locations outside Africa, including the Middle East, Eastern Europe, and Asia. To assess the genetic diversity of LSDVs in East Africa, we sequenced and analyzed the RPO30 and GPCR genes of LSDV in twenty-two archive samples collected in Ethiopia, Kenya, and Sudan before the appearance of LSD in the Middle East and its incursion into Europe. We compared them to publicly available sequences of LSDVs from the same region and those collected elsewhere. The results showed that the East African field isolates in this study were remarkably similar to each other and to previously sequenced field isolates of LSDV for the RPO30 and GPCR genes. The only exception was LSDV Embu/B338/2011, a field virus collected in Kenya, which displayed mixed features between the LSDV Neethling vaccine and field isolates. LSDV Embu/B338/2011 had the same 12-nucleotide insertion found in LSDV Neethling and KS-1 vaccines. Further analysis of the partial EEV glycoprotein, B22R, RNA helicase, virion core protein, NTPase, and N1R/p28-like protein genes showed that LSDV Embu/B338/2011 differs from previously described LSDV variants carrying the 12-nucleotide insertion in the GPCR gene. These findings highlight the importance of the constant monitoring of genetic variation among LSDV isolates.